Development of smart pv travel phone charger - Nik Mohd Farid, Nik Ibrahim (2012)
Solar energy is a one of the alternative renewable energy resource. The energy resource which directly produced by the sun can be converted to electricity by using solar cell. The applications that using photovoltaic technology is a solar cell phone travel phone charger. Solar cell phone charger can save energy compared to electric socket cell phone charger besides not contributing to environmental pollution. The weakness of this type of energy is it‟s depending on the existence or the brightness of sunlight. The project aims to develop charging cell phone using Photovoltaic (PV) otherwise to minimize electricity energy usage. The project also includes different from conversional phone charger due to this travel phone charger have storage battery to always be used when needed at certain times. In addition, this project using the buck converter circuit to monitor the voltage level of the continuous at rated 5 Volt even of the input voltage from solar cell is constantly changing. If the voltage from solar cell exceeds the permissible limits, its will be stabilized by using solar charge controller (SCC) to maintain and the voltage can be set to normal state using LM 2574 as step-down converter function. Thus the device will obtain a continuous power and protected from the effects of under voltage and overvoltage. Furthermore, this travel phone charger is also equipped PIC16F688 for the display using LCD in order to reading of the storage battery can always be observed during the running.